Attitudes and behaviors towards clinical guidelines: the clinicians' perspective. Issue 4 (December 1995) - Mansfield, C D
Abstract : Objectives--To find out what attitudes hospital doctors have towards the culture of clinical guidelines; to ascertain perceived knowledge and use of clinical guidelines; and to investigate why hospital doctors think that clinical guidelines may not be used and how they think that the use of guidelines can be encouraged. Design--Postal questionnaire survey be tween October 1993 and January 1994. Setting--Hospitals within Oxford region. Subjects--409 doctors of all grades working in one of six specialties (anaesthetics, paediatrics, general surgery, general medicine, obstetrics and gynaecology and accident and emergency medicine). 47 were randomly picked as part of the pilot study, 362 were extracted from hospital staffing lists. Results--268 clinicians (66%) responded to the questionnaire. Most respondents (77%, 208) expressed welcoming attitudes towards guidelines but 51%(136) perceived the attitudes of their colleagues as being less favourable. Over three quarters of respondents claimed to use guidelines at least once a month. Most respondents learnt about guidelines from discussions with their peers (50%, 134 respondents) or senior doctors 37%, 99) or from journals (39%, 105). Reasons why guidelines may not be used included being unaware of particular guidelines (80%, 213 respondents) and the fact that guidelines had been poorly developed (64%, 171) or were impractical (49%, 132). The best ways to encourage the use of guidelines were thought to be encouragement from senior doctors (72%, 193 respondents) and peers (59%, 157) and by monitoring behaviour and providing feedback (68%, 181). Conclusion--The decision to use a guide line was based on the perceived value of each guideline and was influenced by other clinicians' behaviour. The results provide an insight into aspects of dissemination and implementation which are perceived as influential by the recipients of guidelines.